Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages 2. Local government. Health Centres. Maternity and Child Welfare. Health visitors and home nursing. Midwifery (outside hospitals). Mental health (outside hospitals). Vaccination and immunisation. Ambulances (except those attached to hospitals). Domestic help. 3. Local Executive Councils. Family doctor. Dentists. Pharmacists. (Half the members of these Councils are nominated by the Minister and the major local authorities, and the other half by elected representatives of the local professions concerned). Hospitals Generally speaking the hospitals and their assets will be taken over by the Minister. Special provision is made for teaching hospitals which will give them a degree of independence similar to that enjoyed by the Universities to-day. Great is the outcry of the British Hospitals Association against this very necessary step without which, however, it is difficult to see how the Minister could accept responsibility for the efficient development and co-ordination of the hospitals of this country. In particular "State robbery" is alleged in that money given by local philanthropists for the local hospital may be diverted to a more needy hospital in another area. This propaganda is financed from voluntary hospital funds. A large proportion of these funds is contributed by workers who thought their money was going to fight disease and not the proposals of the government they had elected. The Family Doctor Vital as are the hospital and specialist services, the acid test of the scheme, however, will be the impression it makes on the vast majority of people who, from time to time, need the services of a doctor or dentist or midwife but rarely, if ever, need in-patient 11 15X/2/98/21